Expected Credit Losses as a Key Driver of Profit Variability in Banks: Ekspektasi Kerugian Kredit sebagai Pendorong Utama Variabilitas Laba Bank - Akdh, Sadam Hamdan; Hasen, Ali Mahmood (Academia Open, 2025)
General Background: In the wake of adopting IFRS 9, commercial banks are required to apply a forward-looking approach in estimating credit losses, aiming to enhance financial transparency and risk management. Specific Background: Iraqi private commercial banks have faced significant challenges in adapting to this paradigm, particularly due to volatile economic conditions and operational inefficiencies. Knowledge Gap: Despite IFRS 9’s relevance, limited empirical analysis exists on how expected credit losses (ECL) affect profitability in emerging markets like Iraq. Aims: This study investigates the impact of ECL on net profit among a sample of Iraqi private commercial banks between 2021 and 2023, focusing on compliance with IFRS 9 and its effect on financial performance. Results: The findings reveal that higher ECLs significantly reduce net profits, especially in banks with high default rates and inconsistent risk practices. Additionally, discrepancies in IFRS 9 compliance contributed to inaccuracies in loss estimations. Novelty: Unlike previous research, this study provides a detailed sector-specific empirical analysis linking regulatory standards to profitability outcomes in a high-risk economic environment. Implications: Strengthening compliance with IFRS 9, enhancing disclosure, and reforming regulatory provisions could mitigate the adverse effects of ECL on profit, thereby reinforcing financial stability in Iraq’s banking sector. Highlights: IFRS 9 impact – Adoption of IFRS 9 led to a forward-looking loss model, affecting how banks recognize credit losses and report profits. Profit reduction – Higher expected credit losses correlate directly with decreased net profits, especially in banks with weak credit risk management. Disclosure gaps – Variations in compliance and lack of transparency in financial disclosures hinder effective decision-making and risk evaluation Keywords: Expected Credit Losses, IFRS 9, Net Profit, Private Banks, Credit Risk